21st century librarian lead to an effective academic library services & development / Hasniza Hassim - Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2018)
The study discovering library profession that contributes to the professional development in academic libraries. The purpose is to find out the strategies that librarians should consider in improving the accomplishment of ICT in operating the libraries. Hence, the study also carried out to determine the level of knowledge and skills required to be a professional librarian, as well as to explore the roles of academic librarians in providing the extension services to the library. In spite of the fact that running an academic library is now supposed to be much more sophisticated than before, the assistance of computerized systems seems to be extra demanding.